Penerapan Metode Design Thinking Pada Model Perancangan UI Dan UX Aplikasi Keuangan Berbasis Mobile - Arip Irwansyah; Didi Juardi; Ryan Ardian (Peneliti.net, 2023)
The role of information and communication technology in today's digital era is very important which has brought about many transformations in all fields. Among them are in the economic and financial fields. With the presence of this technology, it will certainly be easier for economic actors to conduct transactions with financial technology. The scope of financial technology includes all types of innovation related to finance. Its scope includes traditional financial institutions, start-ups, technology development, consumer finance and government. Based on current advances in financial technology, the authors conducted research related to the application of the design thinking method to UI and UX design models for mobile-based financial applications. This research was conducted using the stages of design thinking. Starting from the process of empathizing, defining problems, generating ideas, making prototypes, and testing prototypes. The result of this study is testing the usability of the prototype to get an SUS score of 87 which is included in the acceptable category with a total of 5 respondents.